Solar heater system to disinfect seeds - Muhamad Awang, Rita; Elbashier Elhadaa, Ragaa Mohammed; Grozeccu, Ionel Valeriu; Omar, Dzolkifli; Sinniah, Uma Rani (2012)

(untitled)
A solar heater box for treatment of seeds which comprise of a layered reflective surface having a square-based pyramid frustum shape, wherein the inner layer and of the surface reflects and focuses radiant energy into a receiving platform, providing substantially uniform heating along the receiving platform, wherein the outer layer and of the solar heater is adapted to provide thermal insulation to the solar heater box.